Uso da furazolidona no tratamento clínico de cães com leishmaniose tegumentar americana - Barcellos, Márcio Paiva (2013)
American cutaneous leishmaniasis (ACL) is a widespread disease in several countries. As recommended by the Brazilian Ministry for Health, a treatment of animals is contraindicated. The aim of this study was to test the use of furazolidone (FZ) to treat lesions in dogs suffering from ACL. The study was conducted with nine dogs with lesions and the presence of ACL as confirmed by ELISA and PCR for biopsy and culture for Leishmania (V.) braziliensis. The drug was administered orally in a concentration of 20 mg / kg every twelve hours for seven days, in three steps with an interval of 10 days, accompanied by laboratory monitoring of hematological and biochemical patterns. A regression of the lesion was observed in seven animals. FZ has proven an effective drug in the remission of lesions in dogs with ACL injury